Inhibition by acetaldehyde of the pyruvate dehydrogenase complex from ox brain and ox kidney (Short Communication) - Blass, John P. (1973)
Low concentrations of acetaldehyde, similar to those that can occur in the brain of ethanol-treated animals, effectively inhibit the pyruvate dehydrogenase complex purified from ox brain or from ox kidney, although the precise mechanism of this inhibition remains to be defined.